Penerapan Konsep Metodologi Pendidikan Pada Peserta Didik - Wati, Lilis (MADINAH, 2021)
The purpose of this study was to determine the program, implementation of educational methodologies in the learning process. using a descriptive research method with a qualitative type. with data collection techniques through observation, interviews, and documentation. With the subject of teacher research. Analyze data by reducing data, displaying data, and drawing conclusions. Based on the results of the study, it was shown that: 1) teachers at MIN 1 Nagan Raya carried out several teaching methods such as individual approaches, giving freedom to students, approaching the environment, going global, seeing students' talents and interests. , motivate, teach in real form. 2) the teacher really understands the basics that must be considered such as social, previous studies (historical), cultural differences, religion, existing rules (law) and child behavior (teachers must at least be able to understand the character of their students), several other things.